Improving the Safety of Left-Turn Operations at Signalized Intersections for High-Risk Groups - Abdel-Rahim, Ahmed; Gonzalez, Angel (My University, 2018)
A total of 1,062 left-turn related crashes at signalized intersections in Idaho (2006-2015) were analyzed to document the underlying factors that affect left-turn crashes and to identify crash types that prevail among different driver groups. Comparative analysis was conducted to compare the characteristics of intersections at which frequent crashes occurred and those at which few crashes occurred to identify intersection design and control elements that might have contributed to left-turn crashes. The research results showed that no significant difference in left-turn crashes between intersections that used a flashing yellow arrow and intersections that used a doghouse left-turn signal display. The study results suggested that there is there is a need for more emphasis on left-turn permissive operations at signalized intersections in teen driver education programs, as teen drivers represent the most vulnerable group. Protected-only left-turn operations at signalized intersections on routes and in neighborhoods with greater numbers of mature drivers can eliminate significant portion of mature drivers’ left-turn related crashes. Protected-only left-turn operations at signalized intersections during inclement weather conditions can eliminate a significant portion of the 8 percent of the crashes that occur during inclement weather.
Keywords: Transportation Safety; Operations; Intersections